PENGARUH STRUKTUR MODAL, KINERJA KEUANGAN, PERTUMBUHAN DAN UKURAN BANK TERHADAP NILAI BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Vebry Charolina; Eddy Suranta (UNIB Press, 2022)
This study aims to provide empirical evidence of the influence of capital structure, financial performance, growth, and bank size on the value of Islamic banks listed on the Indonesia Stock Exchange (IDX) using the observation period from 2014 - 2019. Data collection methods using a purposive sampling method using quarterly financial statement data so that the number of observations amounted to 29 observations. The test results show that the ratio of capital structure (DER) and financial performance (ROA) as a proxy for financial performance affect the value of Islamic banks while the growth and size of the company does not affect the value of Islamic banks.